Positive solutions to a class of random operator equations and applications to stochastic integral equations - Jleli, Mohamed; Samet, Bessem (Nonlinear Analysis: Modelling and Control, 2014)
We study the existence of random positive solutions to a random operator equation on ordered Polish spaces. We apply the results obtained in this paper to study the existence of random positive solutions to some classes of stochastic integral equations.